Deteksi dini gangguan pertumbuhan pada bayi risiko tinggi melalui monitoring berat badan: A systematic review - Kurniasih, Dwi Uji; Ramawati, Dian (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
Background: Detection of growth disorders in high-risk infants is done by monitoring weight, length, and head circumference. It is important to monitor newborn weight as a first step in detecting growth disorders in both healthy and sick infants, as well as high-risk infants. Purpose: To detect early detection of disorders in high-risk infants through weight monitoring. Method: Systematic literature review research uses the PICO approach, namely P (problem, patient, or population), I (intervention, prognostic factor, or exposure), C (comparison or control), and O (outcome). Writing literature with keywords “early detection AND growth disorders”, “monitoring AND high risk infants AND weight”, “monitoring weight AND high risk infants”. Identifying 11 articles and then filtering according to the topic of discussion, there were 5 articles related to early detection of disorders in high-risk infants through weight monitoring. Results: Based on the 5 articles reviewed, it shows that monitoring can be applied with several methods, including using WHO growth charts for full-term neonates and Fenton charts for less-term neonates. Conclusion: With early detection by electronic weight method, it becomes easier to manage the failure of weight gain. Suggestion: Neonatal Intensive Care Unit (NICU) nurses can apply the use of daily weight monitoring charts to neonates, especially high risk neonates. Keywords: Baby's Weight; Early Detection; High Risk Infants; Low Weight Babies (LBW); Monitoring; Growth. Pendahuluan: Deteksi gangguan pertumbuhan pada bayi yang berisiko tinggi dilakukan dengan memantau berat badan, panjang badan, dan lingkar kepala. Pentingnya memantau berat badan bayi baru lahir sebagai langkah awal dalam mendeteksi gangguan pertumbuhan, baik pada bayi yang sehat maupun yang sakit, serta bayi berisiko tinggi. Tujuan: Untuk melakukan deteksi dini gangguan pada bayi berisiko tinggi melalui monitoring berat badan. Metode: Penelitian sistematik literature review menggunakan pendekatan PICO yaitu P (problem, patient, or population), I (intervention, prognostic factor, or exposure), C (comparison or control), dan O (outcome). Penulisan literature dengan kata kunci “deteksi dini AND gangguan pertumbuhan”, “monitoring AND high risk infants AND weight”,”monitoring weight AND high risk infants”. Mengidentifikasi 11 artikel selanjutnya dilakukan penyaringan sesuai dengan topik bahasan mendapatkan 5 artikel yang terkait mengenai deteksi dini gangguan pada bayi berisiko tinggi melalui monitoring berat badan. Hasil: Berdasarkan 5 artikel yang dikaji menunjukan bahwa, monitoring tersebut dapat diaplikasikan dengan beberapa metode antara lain, menggunakan grafik pertumbuhan WHO untuk neonatus cukup bulan dan grafik Fenton untuk neonatus kurang bulan. Simpulan: Adanya deteksi dini dengan metode berat badan elektronik, kegagalan peningkatan berat badan akan lebih mudah untuk dilakukan tatalaksana. Saran: Perawat ruang Neonatal Intensive Care Unit (NICU) agar dapat menerapkan penggunaan grafik monitoring berat badan harian pada neonatus, khususnya neonatus risiko tinggi. Kata Kunci: Berat Badan Bayi; Bayi Risiko Tinggi; Bayi dengan Berat Badan Rendah (BBLR); Deteksi Dini; Monitoring; Pertumbuhan.